2020
DOI: 10.1002/hep.31414
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Dysfunction Activates p53 and Represses HNF4α Expression Leading to Impaired Human Hepatocyte Development and Function

Abstract: BaCKgRoUND aND aIMS: Telomere attrition is a major risk factor for end-stage liver disease. Due to a lack of adequate models and intrinsic difficulties in studying telomerase in physiologically relevant cells, the molecular mechanisms responsible for liver disease in patients with telomere syndromes remain elusive. To circumvent that, we used genome editing to generate isogenic human embryonic stem cells (hESCs) harboring clinically relevant mutations in telomerase and subjected them to an in vitro, stage-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…Taken together, these results indicate that telomerase dysfunction results in disrupted hepatic development and abnormal hepatocyte proliferation. Our findings are largely consistent with a recent study modeling DC phenotypes in human ES-derived hepatocytes 7 .…”
Section: Generation and Characterization Of DC Patient-derived Ips Cell-based Hepatocyte And Hepatic Stellate Cell Modelssupporting
confidence: 93%
“…Taken together, these results indicate that telomerase dysfunction results in disrupted hepatic development and abnormal hepatocyte proliferation. Our findings are largely consistent with a recent study modeling DC phenotypes in human ES-derived hepatocytes 7 .…”
Section: Generation and Characterization Of DC Patient-derived Ips Cell-based Hepatocyte And Hepatic Stellate Cell Modelssupporting
confidence: 93%
“…While most data generated to date detailing human cells’ response to genetic instability has been derived from terminally differentiated cells, patients with reduced DNA repair capability or reduced telomere maintenance potential commonly show defects in stem or progenitor cells ( Armanios and Blackburn, 2012 ; Fok et al, 2017 ; Munroe et al, 2020 ; Shukla et al, 2020 ). Successful approaches to restore tissue function in these patients must therefore derive from studies that take into consideration the intrinsic differences between stem cells and their differentiated progenies.…”
Section: Resultsmentioning
confidence: 99%
“…21,93 Recently, Munroe et al using induced hepatocyte-like cells, showed that repression of HNF4α function leads to shortening in telomere length. 94 Argemi et al found that livers from patients with alcoholic hepatitis showed downregulation of HNF4α and they proposed that HNF4α deregulation is in part transforming growth factor β (TGFβ1)-mediated. Moreover, Huang et al showed that upregulation of HNF4α in obese rats with fatty livers led to a significant improvement in serum lipids and glucose homeostasis.…”
Section: Transcriptional Reprogramming Of Hepatocytes End-stage Liver Diseasementioning
confidence: 99%